The Small Group Discussion Health Education Model for Improving Adolescent Knowledge About HIV / AIDS in High Schools in Kerambitan District, Tabanan Regency - Ketut Surinati, I Dewa Ayu; ., Suratiah; Ruspawan, I Dewa Made; Hartati, Ni Nyoman; Runiari, Nengah; Ribek, Nyoman (Journal of Education Research and Evaluation, 2019)
The level of knowledge of adolescents about HIV / AIDS in Indonesia by category is not large enough, which is 48.9%. The small group discussion / SGD learning model is one of the learning steps implemented so that the goal of learning outcomes is quickly achieved more effectively and efficiently. The purpose of this study was to determine the effectiveness of the SGD health education model in increasing adolescent knowledge about HIV / AIDS in high schools in Kerambitan District, Tabanan Regency. The research method used was a pre-experimental design with one-group pre-test - post test design. The sample technique used was random sampling with a total of 100 students. The statistical test used Wilcoxon test. The results showed that the small group discussion education model was effective in increasing adolescent knowledge about HIV AIDS in Kerambitann Tabanan High School, with a value (p) of 0,000.